The Impact of COVID-19 on Foreign Investors : Evidence from the Quarterly Global MNE Pulse Survey for the Fourth Quarter of 2020 - Saurav, Abhishek; Kusek, Peter; Kuo, Ryan; Viney, Brody (World Bank, Washington, DC, 2021)
A fourth round of the quarterly pulse survey, reflecting the last quarter of 2020, was administered in February 2021. This round of the survey included new questions reflecting on 2020, and the impacts of the crisis on technology adoption and environmental sustainability trends. The report’s findings will help provide policy makers and businesses with an updated picture of the effects of the COVID-19 crisis on MNEs and the global outlook for foreign investment. The report’s findings will help provide policy makers and businesses with an updated picture of the effects of the COVID-19 crisis on MNEs and the global outlook for foreign investment.